Primordial black holes formation from particle production during inflation - Erfani, Encieh [UNESP] (IOP Publishing, 2016)
We study the possibility that particle production during inflation can source the required power spectrum for dark matter (DM) primordial black holes (PBH) formation. We consider the scalar and the gauge quanta production in inflation models, where in the latter case, we focus in two sectors: inflaton coupled i) directly and ii) gravitationally to a U(1) gauge field. We do not assume any specific potential for the inflaton field. Hence, in the gauge production case, in a model independent way we show that the non-production of DM PBHs puts stronger upper bound on the particle production parameter. Our analysis show that this bound is more stringent than the bounds from the bispectrum and the tensor-to-scalar ratio derived by gauge production in these models. In the scenario where the inflaton field coupled to a scalar field, we put an upper bound on the amplitude of the generated scalar power spectrum by non-production of PBHs. As a by-product we also show that the required scalar power spectrum for PBHs formation is lower when the density perturbations are non-Gaussian in comparison to the Gaussian density perturbations.
Keywords: ination; primordial black holes